Reconstruction of the Character Education Concept Based on Tazkiyat al-Nafs in Ihya’ Ulum al-Din by Abu Hamid al-Ghazali as a Response to the Moral Crisis of the Digital Generation - Miftakhul Rohman (Attanwir : Jurnal Keislaman dan Pendidikan, 2026)
This study aims to reconstruct the concept of character education based on tazkiyat al-nafs as articulated in Ihya’ Ulum al-Din by Abu Hamid al-Ghazali and to reinterpret its relevance in addressing the moral crisis of the digital generation. The rapid development of digital technology has significantly transformed patterns of communication, learning, and social interaction among adolescents, while simultaneously increasing the risks of ethical deviation, impulsive behavior, and declining moral awareness. Many contemporary character education programs emphasize rule-based digital literacy; however, they often fail to cultivate deep internal moral consciousness. This research employs a qualitative approach using a library research design, with primary data drawn from Ihya’ Ulum al-Din and supported by relevant contemporary scholarly sources. Data were analyzed through content analysis and hermeneutic interpretation to reconstruct Al-Ghazali’s conceptual framework within the context of modern educational challenges. The findings reveal that Al-Ghazali’s model of moral formation is fundamentally centered on the purification of the heart as the core of human behavior. The stages of takhalli (eliminating blameworthy traits), tahalli (cultivating praiseworthy virtues), and tajalli (manifesting divine values in conduct) represent a systematic and transformative pedagogical process. This framework integrates cognitive understanding, ethical practice, and spiritual discipline, aligning with contemporary concepts of self-regulation and reflective awareness. The study concludes that reconstructing character education based on tazkiyat al-nafs provides a holistic, theoretically coherent, and pedagogically applicable model for fostering morally conscious, emotionally balanced, and digitally responsible individuals in the modern era.